Social action in the South African Constitution - Naudé Malan (Acta Academica, 2014)
Social action, as a key concept in social theory, is used in this article to understand the extent to which social actors can intervene in society in order to address economic inequalities. This article clarifies the place of social action in social theory and in a select number of socio-economic rights cases. These bring into view an emphasis on state, market and civil society actors, as well as individuals. The article identifies and clarifies how such actors and actions are supported and regulated by the South African rights regime. This has implications for the notion of core-content to rights and the nature of relief sought through a claim on rights; for the participation of citizens in welfare and other state programmes, and for the compensation rights-actors may expect from the state for taking social action. The article concludes by identifying key themes that concern social action in the South African rights regime.